Characterization of methyl-accepting chemotaxis proteins (MCPs) for amino acids in plant-growth-promoting rhizobacterium Pseudomonas protegens CHA0 and enhancement of amino acid chemotaxis by MCP genes overexpression. Issue 9 (1st September 2020) - Hida, Akiko; Oku, Shota; Miura, Manami; Matsuda, Hiroki; Tajima, Takahisa; Kato, Junichi
ABSTRACT: Pseudomonas protegens CHA0, known as plant-growth-promoting rhizobacterium, showed positive chemotactic responses toward proteinaceous L-amino acids. Genomic analysis revealed that P. protegens CHA0 possesses four putative chemoreceptors for amino acids (designated CtaA, CtaB, CtaC, and CtaD, respectively). Pseudomonas aeruginosa PCT2, a mutant defective in chemotaxis to amino acids, harboring a plasmid containing each of ctaA, ctaB, ctaC, and ctaD showed chemotactic responses to 20, 4, 4, and 11 types of amino acids, respectively. To enhance chemotaxis toward amino acids, we introduced the plasmids containing ctaA, ctaB, ctaC, or ctaD into P. protegens CHA0. By overexpression of the genes, we succeeded in enhancing chemotaxis toward more than half of the tested ligands. However, unexpectedly, the P. protegens CHA0 transformants showed unchanged or decreased responses to some amino acids when compared to wild-type CHA0. We speculate that alternation of expression of a chemoreceptor may affect the abundance of other chemoreceptors. Abbreviations: cDNA: complementary DNA; LBD: ligand-binding domain; MCP: methyl-accepting chemotaxis protein; PDC: PhoQ/DcuS/CitA; PGPR: plant-growth-promoting rhizobacteria; qRT-PCR: quantitative reverse transcription PCR GRAPHICAL ABSTRACT: Four chemotaxis sensors for amino acids in PGPR Pseudomonas protegens CHA0. Amino acid chemotaxis can be enhanced by overexpression of the genes.